Strategi Minimalisasi Economic Losses Pada Industri Jasa Makanan: Pencegahan Pemborosan Pangan Di Bogor (Jurnal Agribisnis Indonesia, 2025)
Food wastage is a major challenge in achieving global food security, especially with the increasing demand for food due to population growth. The food service industry sector has a significant contribution to food wastage, which results in economic losses and environmental sustainability. The objective of this study is to estimate food wastage from the food service industry, especially restaurants in Bogor City, and recommend strategies that can be implemented to minimize it. Data were collected from 13 restaurants in Bogor City based on SNI 19-3964-1994 guidelines, food waste was calculated using food weighing and conversion factors, then strategies to reduce food waste were formulated using the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method. The results showed that the average restaurant in Bogor City produces food waste of 1.56 kg/day, which consists of 67.6% still classified as avoidable food waste and the rest including unavoidable food waste. Analysis using TOPSIS shows that the best strategy recommendations that can be applied by restaurant managers in minimizing food waste are; 1) donating food waste to people in need; (2) planning the amount of food to be made and planning in purchasing raw materials; (3) inventory management and updating appropriate technology; (4) utilizing food waste as feed for the food industry; (5) using food waste as feed for the food industry; (6) using food waste as feed for the food industry; and (7) using food waste as feed for the food industry.